Unicorn - Lloyd, Clare; Glavin, Kitty (New York, New York DK Publishing, 2019)
"Can you find the magical unicorns hiding under the flaps?"--Page 4 of cover
Rhymes and songs
1 2
Keywords: Lift-the-flap books -- Specimens; Stories in rhyme